2019
DOI: 10.1111/ijlh.13055
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in MAPK9 (rs4147385) and CSF1R (rs17725712) are associated with the development of inhibitors in patients with haemophilia A in North China

Abstract: Introduction The formation of neutralizing antibodies (FVIII inhibitors) in haemophilia A patients is an immune response to the deficient factor. This process is multifactorial and includes environmental and genetic factors. Some genetic markers that play a decisive role in the immune response have been identified as risk factors for inhibitor development. Objective Our aim was to investigate the association between polymorphisms in several genes involved in the regulation of the immune response and inhibitor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
3
0
1
Order By: Relevance
“…It has been found that MAPK signaling pathway is involved in cell malignant phenotypes, including cell proliferation, cell differentiation and cell migration [ 20 ]. As a key member in the MAPK signaling pathway, MAPK9 is also correlated with several diseases, including non-small-cell lung carcinoma [ 21 ], haemophilia A [ 22 ], and type I diabetes [ 23 ]. Through our investigation, MAPK9 was discovered to be a downstream target of miR-514a-5p.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that MAPK signaling pathway is involved in cell malignant phenotypes, including cell proliferation, cell differentiation and cell migration [ 20 ]. As a key member in the MAPK signaling pathway, MAPK9 is also correlated with several diseases, including non-small-cell lung carcinoma [ 21 ], haemophilia A [ 22 ], and type I diabetes [ 23 ]. Through our investigation, MAPK9 was discovered to be a downstream target of miR-514a-5p.…”
Section: Discussionmentioning
confidence: 99%
“…In autoimmune diseases, polymorphisms in the immune response genes were reported to be related to the formation of antibody. In addition, SNPs in the regulatory regions of cytokine genes are crucial components in the pathogenesis of various diseases, including HA [21,22]. Individual immune response traits might in uence a patient's reaction to exogenous factor VIII.…”
Section: Discussionmentioning
confidence: 99%
“…Todos eles relacionados à apresentação de peptídeos de FVIII às células CD41 T-helper. Alguns polimorfismos genéticos, como os do TGF-β, da e IL10, em CD44, receptor de fator 1 estimulante de colônias (CSF1R), DOCK2, proteína MAPK9 e IQGAP2 os genes TNFalfa e CTLA4 foram sugeridos em alguns estudos como contribuintes ao risco de inibidor na hemofilia A, contudo o estudo que evidenciou essas relações envolveu poucos indivíduos (Astermark, 2015;Lai et al, 2016;Naderi et al, 2018;Zhao et al, 2019).…”
Section: Prevalência E Fatores De Risco Para O Desenvolvimento De Ini...unclassified